Family caregivers’ experience in the process of caring for older adults: a qualitative synthesis (Research, Society and Development, 2021)
In this review, the main goal was to answer the question: What are the family caregivers’ experiences in the process of providing care to older people? To do so, a systematic literature review was carried out by consulting the MEDLINE, Cochrane, and Lilacs databases. Two reviewers selected the studies independently, and discrepancies were sorted out by a third reviewer. The Critical Appraisal Skills Programme was used to evaluate the methodological quality of the included studies, and thematic analysis was applied to synthesize the results. The analytical themes addressed in the synthesis were developed through researchers’ interpretations and new constructs. Confidence in the findings was reviewed using GRADE-CERQual. The study adhered to Enhancing Transparency in Reporting the Synthesis of Qualitative Research guidelines. Eighteen studies were included in the synthesis. Three analytical themes emerged: "Mixed feelings", "You have no life. Your own life gets put on hold”, and "The need for increasing coping strategies". Several conflicting feelings emerged in the process of care, showing the complexity of the caregivers’ experience. Either way, the caregivers put their lives on hold to provide care and sought coping strategies, such as formal and informal support and spirituality. Therefore, both health professionals and policymakers must ensure comprehensive care for the older adults and their families, so that caregivers do not compromise their own lives and health in order to take care of others.